Analysis of the Influence of Marine Tourism on Coastal Development in Serdang Bedagai Regency (Mirror Beach District Case Study) - Trisuyadi, Andri; Sirojuzilam, Sirojuzilam; Lubis, Suwardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to analyze the influence of marine tourism business factors on the income of marine business actors in Pantai Cermin District of Serdang Bedagai Regency and the Impact of the Covid 19 Virus Pandemic on the income of marine business actors in Pantai Cermin District of Serdang Bedagai Regency. The research was conducted in Serdang Bedagai Regency on the analysis of the influence of marine tourism on the development of coastal areas in Serdang Bedagai Regency (Case study of Pantai Cermin District). The analytical methods used in this study are multiple regression analysis and test analysis different t with the number of respondents as many as 82 people. The results of the study obtained that capital factors, the number of workers, places of business, formal education, informal education, and the legality of business entities simultaneously affect the income of marine business actors in Pantai Cermin District. Partially variable capital, and the number of workers shows a significant influence on the income of marine business actors in Pantai Cermin District. While the dummy variables of business premises, formal education, informal and legality of business entities do not show a significant influence on the income of marine business actors in Pantai Cermin District. The Covid 19 pandemic shows a negative impact, namely a decrease in the income of marine businesses.